(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Technological advancements are revolutionizing the highly competitive hotel and restaurant industries, driving improvements in service quality and attracting guest interest. The Hotel and Restaurant Management System (HRMS) offers an integrated solution, including digitalized inventory management, designed to meet the specific needs of these sectors. However, many hotels still rely on outdated methods, leading to inefficiencies and security vulnerabilities. This project seeks to address these issues by implementing RFID sensors for enhanced door security, an automated inventory management system for precise tracking of hotel supplies, and digital platforms for housekeeping and maintenance requests. The objective is to create a fully integrated, digitalized system that enhances operational efficiency, improves security, and ultimately delivers a better experience for both employees and guests. The Agile Scrum methodology focuses on fostering trust and collaboration within teams, enabling them to work directly with customers to understand their needs and provide timely, effective solutions. Each sprint is dedicated to developing specific features, allowing for continuous progress and improvement. Regular scrum meetings ensure adaptability, transparency, and strong communication, enabling teams to respond quickly to changes and challenges. The project manager plays a crucial role in overseeing the project’s scope, managing day-to-day operations, and supporting both the project team and sponsor. Beyond ensuring the project’s successful execution, the project manager also helps the team generate leads, contributing to the overall growth and success of the company. This project aims to enhance housekeeping and maintenance services by integrating a digital request system with an RFID-based door locking system and an automated inventory management system. Guests can conveniently submit housekeeping and maintenance requests digitally via their mobile devices, improving responsiveness and customer service. The RFID door locking system ensures heightened security, while the automated inventory management streamlines tracking and management of hotel supplies. By digitizing these processes, the project not only improves operational efficiency but also elevates the overall guest experience, delivering seamless, timely, and secure services. The integration of technologies such as an automated inventory management system and an RFID-based door locking system into a unified digital request platform for housekeeping and maintenance has significantly streamlined operations and enhanced service delivery. Two key lessons learned from this project’s implementation are the importance of establishing clear project objectives and conducting a thorough needs analysis. These steps are essential for aligning the project with stakeholder expectations and ensuring its success. Additionally, fostering collaboration between the project team, stakeholders, scrum master, and end users is critical for incorporating diverse perspectives, addressing all needs, and ensuring the solution is both effective and comprehensive.